Tumoral Melanosis: A Case Series of a Rare Clinical Entity - Cesare Ariasi; Grazia Linda Artelli; Cristina Zane; Martina Perantoni; Simone Soglia; Giuseppe La Rosa; Vincenzo Maione; Marina Venturini; Claudia Zambelli; Gaetano Licata; Mariateresa Rossi; Mariachiara Arisi (Dermatology and Therapy)
Abstract Tumoral melanosis (TM) is a rare entity thought to result from the complete regression of melanoma. Clinically, TM resembles malignant melanocytic lesions, presenting as hyperpigmented flat or papulonodular lesions. Histologically, TM lacks melanocytes, instead showing inflammation, fibrosis, and melanophages. Diagnosing melanoma without melanocytes is challenging, and TM may also represent other regressed benign or malignant pigmented lesions. This study retrospectively analyzed 12 TM cases focusing on the clinical course, management, and potential for malignancy. Among the cases, 50% were associated with advanced or metastatic melanoma, supporting TM’s potential as a regressed melanoma. Conversely, in 50% of cases, TM occurred without primary or metastatic melanoma, suggesting possible regression of a benign or malignant epithelial lesion such as pigmented basal cell carcinoma (BCC) or seborrheic keratosis (SK) or confinement of melanoma by the immune system. Management included surgical excision and follow-up similar to that of melanoma. Sentinel lymph node biopsy (SLNB) was selectively performed based on clinical suspicion and multidisciplinary team discussions. In conclusion, TM should be considered potentially regressed melanoma, especially in patients with high disease burden, and the possibility of derivation from high-grade melanomas must always be considered. Given the inability to distinguish TM from completely regressed melanoma, clinicians must remain vigilant and suspect this origin during staging and follow-up. Comprehensive management and close monitoring are crucial to address TM’s clinical implications.